Presocratic philosophy: A very short introduction - Osborne, Catherine (Oxford Oxford university press, 2004)
Generations of philosophers, both ancient and modern, have traced their inspiration back to the Presocratics. Part of the fascination stems from the fact that little of what they wrote survives. Here Osborne invites her readers to dip their toes into the fragmentary remains of thinkers from Thales to Pythagoras, Heraclitus to Protagoras, and to try to reconstruct the moves that they were making, to support stories that Western philosophers and historians of philosophy like to tell about their past.This book covers the invention of western philosophy: introducing to us the first thinkers to explore ideas about the nature of reality, time, and the origin of the universe.